Diet composition of a generalist predator does not indicate its population impact on prey: a response to Pagh et al. (2025) - Peter Sunde; Sari Holopainen; Morten Elmeros; Heidi Krüger; Malin Aronsson; Fredrik Dahl; Kim Jaatinen; Per-Arne Åhlén; Anthony D. Fox (European Journal of Wildlife Research, 2026)

Red deer in confined nature areas have smaller ranges and move less than red deer in unconfined areas - Laura Bonnefond; Martin Mayer; Rasmus Mohr Mortensen; Lars Haugaard; Peter Sunde (Science of The Total Environment, 2025)

A Cost-Benefit Analysis of Alternative Management Strategies for Red Deer in Denmark - Frank Jensen; Thomas Lundhede; Peter Sunde (Environmental Management, 2024)
In this paper, we conduct a cost-benefit analysis (CBA) of five alternative management strategies for red deer in Denmark: free harvest, trophy hunting, maximum harvest and two cases for natural demographic population compositions. To capture the outcome under each strategy we use a biological sex- and age-structured population model. The net benefit function includes meat values, recreational values, browsing damage costs and traffic damage costs and these values and costs are assumed to differ for the various sex and age classes of red deer. We show that the maximum harvest strategy leads to a reasonably high positive total net benefit, while the free harvest strategy yields a small positive net benefit. On the other hand, the trophy hunting strategy generates a high negative net benefit, while small negative net benefits are obtained under the two strategies for natural demographic population compositions.

Wherever I may roam—Human activity alters movements of red deer ( Cervus elaphus ) and elk ( Cervus canadensis ) across two continents - Steffen Mumme; Arthur D. Middleton; Paolo Ciucci; Johannes De Groeve; Andrea Corradini; Ellen O. Aikens; Federico Ossi; Paul Atwood; Niko Balkenhol; Eric K. Cole; Lucie Debeffe; Sarah R. Dewey; et al. (Global Change Biology, 2023)
Human activity and associated landscape modifications alter the movements of animals with consequences for populations and ecosystems worldwide. Species performing long‐distance movements are thought to be particularly sensitive to human impact. Despite the increasing anthropogenic pressure, it remains challenging to understand and predict animals' responses to human activity. Here we address this knowledge gap using 1206 Global Positioning System movement trajectories of 815 individuals from 14 red deer ( Cervus elaphus ) and 14 elk ( Cervus canadensis ) populations spanning wide environmental gradients, namely the latitudinal range from the Alps to Scandinavia in Europe, and the Greater Yellowstone Ecosystem in North America. We measured individual‐level movements relative to the environmental context, or movement expression, using the standardized metric Intensity of Use, reflecting both the directionality and extent of movements. We expected movement expression to be affected by resource (Normalized Difference Vegetation Index, NDVI) predictability and topography, but those factors to be superseded by human impact. Red deer and elk movement expression varied along a continuum, from highly segmented trajectories over relatively small areas (high intensity of use), to directed transitions through restricted corridors (low intensity of use). Human activity (Human Footprint Index, HFI) was the strongest driver of movement expression, with a steep increase in Intensity of Use as HFI increased, but only until a threshold was reached. After exceeding this level of impact, the Intensity of Use remained unchanged. These results indicate the overall sensitivity of Cervus movement expression to human activity and suggest a limitation of plastic responses under high human pressure, despite the species also occurring in human‐dominated landscapes. Our work represents the first comparison of metric‐based movement expression across widely distributed populations of a deer genus, contributing to the understanding and prediction of animals' responses to human activity.

Correction to: Colonization and habitat selection of a declining farmland species in urban areas - Martin Mayer; Peter Sunde (Urban Ecosystems, 2020)

Colonization and habitat selection of a declining farmland species in urban areas - Martin Mayer; Peter Sunde (Urban Ecosystems, 2020)

Seasonal variation in the sex and age composition of the woodcock bag in Denmark - Thomas Kjær Christensen; Anthony D. Fox; Peter Sunde; Jens Peder Hounisen; Liselotte W. Andersen (European Journal of Wildlife Research, 2017)

Spatial and begging behaviours of juvenile Tawny Owls (Strix aluco) from fledging to independence under contrasting food conditions - Peter Sunde; Pernille Johansen Naundrup (Journal of Ornithology, 2016)

It counts who counts: an experimental evaluation of the importance of observer effects on spotlight count estimates - Peter Sunde; Lonnie Jessen (European Journal of Wildlife Research, 2013)

Seasonal variation in Eurasian Wigeon Anas penelope sex and age ratios from hunter-based surveys - Kevin Kuhlmann Clausen; Lars Dalby; Peter Sunde; Thomas Kjær Christensen; Bjarke Egelund; Anthony David Fox (Journal of Ornithology, 2013)

Seasonal survival rates and causes of mortality of Little Owls in Denmark - Kasper Thorup; Dorthe Pedersen; Peter Sunde; Lars Bo Jacobsen; Carsten Rahbek (Journal of Ornithology, 2013)

Predicting the distribution of Tawny Owl (Strix aluco) at the scale of individual territories in Denmark - Rikke Anker Jensen; Peter Sunde; Gösta Nachman (Journal of Ornithology, 2012)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

Spatial behaviour of little owls (Athene noctua) in a declining low-density population in Denmark - Peter Sunde; Kasper Thorup; Lars B. Jacobsen; Miriam H. Holsegård-Rasmussen; Nina Ottessen; Susanne Svenné; Carsten Rahbek (Journal of Ornithology, 2009)